Studi Numerik Pengaruh Ukuran Penampang, Rasio Tulangan Lentur dan Jarak Tulangan Geser Terhadap Kekakuan Balok Beton Bertulang Menggunakan Program Respone 2000 - Prayuda, Hakas; Saleh, Fadillawaty; Istiawan, Istiawan (Semesta Teknika, 2018)
One of the reinforced concrete beam behavior can be seen from the value of deflection, maximum load, and the relationship between moment with curvature and stiffness of the beam. Respone 2000 program is an approach program with numerical method that can be used to analyze the reinforced concrete beam. The results of this program include the value of deflection, maximum load, moment and curvature. This study aims to obtain numerical results in the form of stiffness of the beam, deflection value, maximum load, moment and curvature until the crack pattern occurs. This research was done by making 32 sample beam with variation of cross section of beam, flexural reinforcement ratio and shear reinforcement distance. The result of the analysis shows that the length of the span has a big effect on the deflection value, the maximum load and the stiffness but not the nominal moment. The results of the reinforcement ratio in this study greatly affect the deflection value, the masimum load, the nominal moment and the stiffness of the beam, while the shear reinforcement distance affects the beam behavior but only on some specimens.